Defective Autophagy in T Cells Impairs the Development of Diet-Induced Hepatic Steatosis and Atherosclerosis - Amersfoort, Jacob; Douna, Hidde; Schaftenaar, Frank H.; Foks, Amanda C.; Kröner, Mara J.; van Santbrink, Peter J.; van Puijvelde, Gijs H. M.; Bot, Ilze; Kuiper, Johan (Frontiers in Immunology, 2018)
Macroautophagy (or autophagy) is a conserved cellular process in which cytoplasmic cargo is targeted for lysosomal degradation. Autophagy is crucial for the functional integrity of different subsets of T cells in various developmental stages. Since atherosclerosis is an inflammatory disease of the vessel wall which is partly characterized by T cell mediated autoimmunity, we investigated how advanced atherosclerotic lesions develop in mice with T cells that lack autophagy related protein 7 (Atg7), a protein required for functional autophagy. Mice with a T cell specific knock-out of Atg7 (Lck-Cre Atg7f/f ) had a diminished naïve CD4+ and CD8+ T cell compartment in the spleen and mediastinal lymph node as compared to littermate controls (Atg7f/f). Lck-Cre Atg7f/f and Atg7f/f mice were injected intravenously with rAAV2/8-D377Y-mPCSK9 and fed a Western-type diet to induce atherosclerosis. While Lck-Cre Atg7f/f mice had equal serum Proprotein Convertase Subtilisin/Kexin type 9 levels as compared to Atg7f/f mice, serum cholesterol levels were significantly diminished in Lck-Cre Atg7f/f mice. Histological analysis of the liver revealed less steatosis, and liver gene expression profiling showed decreased expression of genes associated with hepatic steatosis in Lck-Cre Atg7f/f mice as compared to Atg7f/f mice. The level of hepatic CD4+ and CD8+ T cells was greatly diminished but both CD4+ and CD8+ T cells showed a relative increase in their IFNγ and IL-17 production upon Atg7 deficiency. Atg7 deficiency furthermore reduced the hepatic NKT cell population which was decreased to less than 0.1% of the lymphocyte population. Interestingly, T cell specific knock-out of Atg7 decreased the mean atherosclerotic lesion size in the tri-valve area by over 50%. Taken together, T cell specific deficiency of Atg7 resulted in a decrease in hepatic steatosis and limited inflammatory potency in the (naïve) T cell compartment in peripheral lymphoid tissues, which was associated with a strong reduction in experimental atherosclerosis.